2014
DOI: 10.1111/ejh.12445
|View full text |Cite
|
Sign up to set email alerts
|

Ten‐Eleven‐Translocation 2 (TET2) is downregulated in myelodysplastic syndromes

Abstract: TET2, a member of the ten-eleven-translocation (TET) family genes that modify DNA by converting 5-methylcytosine (5-mC) to 5-hydroxymethylcytosine (5-hmC), is located in chromosome 4q24 and is frequently mutated in myeloid malignancies. The impact of TET2 mutation on survival outcomes is still controversial; however, functional studies have proved that it is a loss-of-function mutation that impairs myeloid cell differentiation and contributes to the phenotype of myeloid neoplasia. We, herein, aimed to investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 18 publications
(27 reference statements)
7
18
0
Order By: Relevance
“…It was shown that TET2 mutations were associated to low 5-hmC counts in DNA. However, Liu et al (2013) [32] demonstrated that TET2 expression decreased in adult patients with MDS regardless of the mutational status, and that expression was positively correlated with 5-hmC value of total DNA [32,33]. In this study we confirmed and produced further evidence of these findings in RCC, one subtype of pediatric MDS.…”
Section: Discussionsupporting
confidence: 68%
“…It was shown that TET2 mutations were associated to low 5-hmC counts in DNA. However, Liu et al (2013) [32] demonstrated that TET2 expression decreased in adult patients with MDS regardless of the mutational status, and that expression was positively correlated with 5-hmC value of total DNA [32,33]. In this study we confirmed and produced further evidence of these findings in RCC, one subtype of pediatric MDS.…”
Section: Discussionsupporting
confidence: 68%
“…25,26 We re-examined normalized mRNA expression in a recent PCa study 9 of 29 matched normal adjacent tissue (NAT) samples, 131 primary tumors, and 19 metastatic tumors. Expression decreased when comparing the NAT with primary tumors but not significantly, but was significant when comparing primary with metastatic tumors (p = 0.01; Figure 2a).…”
Section: Resultsmentioning
confidence: 99%
“…Somatic TET2 mutations have been described in approximately 5% of older individuals without hematologic malignancy (27). However, TET2 mutations have clearly been linked to myeloid dysfunction (28) and clonal disease (29), and, more importantly, responsiveness to hypomethylating agents such as azacitabine or decitabine (30). …”
Section: Discussionmentioning
confidence: 99%